Credit demand in the Irish mortgage market: What is the gap and could public lending help? - Eoin Corrigan; Conor O'Toole; Rachel Slaymaker (The Economic and Social Research Institute (ESRI), 2020)
In this paper, we estimate credit demand for potential Irish first time buyer households currently living in the rental sector. Exploiting individual survey responses to credit demand questions, and characteristics of the household, we estimate the level of latent credit demand that could be serviced by the market given prudent credit risk assessment and the current regulatory environment. We then compare this demand to current market provision to explore whether a credit gap exists. We find evidence of excess demand for credit and an undersupply of loans relative to latent demand. In terms of credit access issues, we find that insufficient savings for a down-payment, rather than income or affordability, is the most binding constraint. Scenario analysis suggests between 2,000 and 9,000 additional loans could be provided per annum depending on the degree to which demand is realised. This would imply an additional exteuro0.4bn to exteuro1.9bn in lending. We show a targeted public mortgage credit instrument could alleviate a portion of this gap and aid market access by providing between 1,100 and 5,800 loans at between exteuro0.2bn to exteuro1bn approximately.
Keywords: R21; G21; R31; R38; 330; Access to credit; macroprudential; mortgages